DIGITAL BUSINESS TRANSFORMATION IN MODEST FASHION: A CASE STUDY OF ASH SCARF - Zenitha Kurnia Putri; Rita Anggraini Rahayu; Budi Eko Soetjipto (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This article investigates the digital transformation journey of Ash Scarf, a local modest fashion brand in Indonesia. Applying qualitative methods, including interviews, field observations, and digital content analysis, the study explores how Ash Scarf adapted to a rapidly shifting digital landscape. Key findings highlight the brand's strategic use of social media, e-commerce platforms, and digital analytics tools to enhance customer engagement and operational agility. Situated within broader theories of digital capability, strategic marketing adaptation, and customer co-creation, the case demonstrates how small enterprises can harness digital tools for survival, expansion, and long-term competitiveness.